The Problem of Timeliness of Young Children Vaccination and Ways to Solve It - I. G. Suetina; Y. Y. Illek; N. V. Khlebnikova; A. Ya. Mindlina; N. P. Galina; A. V. Stepenko (Эпидемиология и вакцинопрофилактика)
Relevance Aims. Despite of widespread achievements and maintenance of appropriate levels of coverage of preventive vaccinations (>95%) the problem of delayed immunizations and vaccination on time is still existed in the Russian Federation over the last years. Materials and methods.  A selective analysis of the vaccination on time against diphtheria, tetanus, pertussis and hepatitis B, of children aged under 2 years in Russia, Moscow, from 2014 to 2018 was conducted. To assess the timeliness of vaccination, two independent sample studies were conducted: the vaccination history of 6003 whooping cough patients in Moscow was analyzed and vaccination was evaluated in 641 children, who were born 2016–2018  in Kirov, depending on the implementation of combination vaccines.  Results.  The current  95% coverage  of preventive  age-recommended vaccination  of decreed  age against  pertussis, diphtheria, tetanus, polio, hepatitis B is achieved only by 2–3 years of age. Conducted analysis showed, that the implementation of combination vaccines contributed  to increase in the proportion  of timely vaccinated children up to 1 year of age as well as propotion of children who started primary immunization series at recommended age of 3 months. Also as a result the vaccination coverage against Hib infection and proportion of timely vaccinated against pneumococcal infection was increased. Conclusions.The implementation of modern multicomponent combination vaccines allows to increase vaccination coverage in population and to control effectively infectious diseases and also to reduce number of injections and visits to clinics.